Konsep Aliran Filsafat Pendidikan (Progresivisme) - Salsabila, Ikrima; Zahirashafa, Alya Ghaitsa; Lestari, Lusiana Amanda (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The flow of progressivism seeks to develop so that humans can survive in facing all of life's challenges. This philosophical school places humans as complete biological creatures and respects the dignity of humans as actors in life. The aim of this journal is to understand the concepts, goals and views of progressivism in learning. The preparation of this journal uses a qualitative approach based on library research or literature study.